Children’s food selectivity: An integrative review (Research, Society and Development, 2023)
Objective: The article aimed to analyze the main causes associated with Children's Food Selectivity (CFS) and discuss the behavioral strategies used to control the condition. Materials and Methods: To prepare this integrative review, articles published in journals indexed in two databases were analyzed: SciELO (Scientific Electronic Library Online) and the VHL portal (Biblioteca Virtual em Saúde). The searches were carried out using the terms feeding difficulties, food selectivity and picky eaters, together with the words children and childhood, in the English language; and eating difficulties, food selectivity, dietary requirements, adjunct to the words children and childhood, for the Portuguese language; using AND and OR as Boolean operators. Results: The results showed that the causes associated with CFS include genetic factors, sensory predispositions and innate preferences for certain flavors and textures. Environmental factors, such as limited exposure to food in early childhood and family habits, proved to be relevant. This condition can be controlled through the association between nutritional and behavioral strategies based on the gradual introduction of new foods and the child's involvement in the process of selecting and preparing meals. Conclusion: CFS is a multifaceted phenomenon, influenced by biological, socioeconomic and cultural factors. Its approach must be multimodal and based on the participation of a professional nutritionist, encouraging the consumption of healthy foods and also parental education.